2021
DOI: 10.1039/d1na00496d
|View full text |Cite
|
Sign up to set email alerts
|

Sound methods for the synthesis of nanoparticles from biological molecules

Abstract: The development of simple, green, reproducible, and scalable approaches for synthesizing nanoparticles from biomolecules is important to advance nanomaterials towards therapeutic applications. Microreactors generated by high frequency ultrasound provide a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Ultrasonication is a technique used to decrease size and increase dispersibility in the extract. This can be occurred as ultrasonic waves produce bubbles and cavities between particles in solutions breaking the weak van der Waals and other attraction forces that cause intra-molecules cleavage and thus, reducing the particles' size that will enhance the absorption of UEERO inside the oocysts [73]. Consequently, the present study revealed that UEERO had an inhibitory anticoccidial effect on sporulation (%) of E. tenella oocysts in a dose dependent manner as compared to control group.…”
Section: Discussionmentioning
confidence: 50%
“…Ultrasonication is a technique used to decrease size and increase dispersibility in the extract. This can be occurred as ultrasonic waves produce bubbles and cavities between particles in solutions breaking the weak van der Waals and other attraction forces that cause intra-molecules cleavage and thus, reducing the particles' size that will enhance the absorption of UEERO inside the oocysts [73]. Consequently, the present study revealed that UEERO had an inhibitory anticoccidial effect on sporulation (%) of E. tenella oocysts in a dose dependent manner as compared to control group.…”
Section: Discussionmentioning
confidence: 50%
“…Herein, we studied the growth mechanism of gold nanostructures with distinct morphologies using tryptophan and ultrasound. Tryptophan was chosen for our experiment due to its reported sono-responsive nature. Subsequently, it was observed that tryptophan itself can reduce gold ions most likely via the oxidation of tryptophan, and the in situ-oxidized tryptophan promoted the anisotropic growth of primary Au nuclei to produce 2-D gold sheets. The gold nanostructures are produced by simply incubating the gold precursor with pristine tryptophan for 72 h, comprised mostly of AuNPs and a few 2-D gold nanosheets (AuNSs) with triangular and hexagonal morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic emulsification is a simple, fast, versatile, and green pathway for preparing PSNE [5] . In previous studies Zhou et al have shown that the active cavitation zone in the flow through horn is limited to the hole region [6] .…”
Section: Introductionmentioning
confidence: 99%